Sciatic Nerve Injury Associated with Acetabular Fractures - Issack, Paul S. (Springer-Verlag, 2008)
Sciatic nerve injuries associated with acetabular fractures may be a result of the initial trauma or injury at the time of surgical reconstruction. Patients may present with a broad range of symptoms ranging from radiculopathy to foot drop. There are several posttraumatic, perioperative, and postoperative causes for sciatic nerve palsy including fracture–dislocation of the hip joint, excessive tension or inappropriate placement of retractors, instrument- or implant-related complications, heterotopic ossification, hematoma, and scarring. Natural history studies suggest that nerve recovery depends on several factors. Prevention requires attention to intraoperative limb positioning, retractor placement, and instrumentation. Somatosensory evoked potentials and spontaneous electromyography may help minimize iatrogenic nerve injury. Heterotopic ossification prophylaxis can help reduce delayed sciatic nerve entrapment. Reports on sciatic nerve decompression are not uniformly consistent but appear to have better outcomes for sensory than motor neuropathy.